การจัดการของประชาชนในการปลูกปาล์มน้ามัน บนพื นที่สาธารณประโยชน์ บ้านเกาะยวน ต้าบลท่ากระดาน อ้าเภอคีรีรัฐนิคม จังหวัดสุราษฎร์ธานี - ช่วงชุ่ม, ปิยวรรณ (Thai Interdisciplinary and Sustainability Review, 2019)
The purpose of this study was to investigate the gathering and management amongst people including problems and obstacles of planting oil palms in a public area of Bankohyuan, Thakada, Khiriratnikhom, Suratthani. 15 of the committee were interviewed and related documents were analysed. The content data analysis, description and conclusion of the objectives were used. The results on studying people gathering to plant oil palms in the public area showed that they realised the benefits of people grouping and shared utilisation of public space in the village. They volunteered to be members and collected internal and external fund to be a capital for oil palm plantation investment. The findings also showed that the management consisted of three aspects. 1) The performance aspect composed of gathering members, and determining objectives, rules and regulations. The frameworks were designed clearly. Monthly meetings were conducted to discuss and try to solve the issues in oil palm plantation development. 2) As for the finance, the internal and external capitals were provided. The accountings of revenues and expenses were made. Acts of paying, receiving and saving the money were conducted. 3) In marketing planning, there were plans of product sales and the market trends were always monitored. Moreover, the study found that there were the problems and obstacles in planting oil palm trees on the public area. At the beginning of the gathering, people did not understand the objectives and lacked of confidence in the formed group. There were also finance problems because they had to pay a lot of money to invest in the palm plantation. A simple accounting of revenues and expenses was designed but it was rather unsystematic. There was distribution problems in marketing aspect. The group chose only to sell to oil palm buyers, which was a monopoly.